Enhancing Security In Device-To-Device Communication Of 5G Networks Through Hybrid Method Using AES And Huffman Encoding. - D. J., Chaithanya; Anitha S, Dr. (Journal of Namibian Studies)
D-2-D (Device to Device) communication is essential in 5 Generation communication networks for allowing communication between devices without transmitting data through the network infrastructure and it plays a major challenge in assuring the effectiveness and security of D-2-D (Device to Device) communication. In this research work, a hybrid method is proposed for the security and effectiveness of Device-to-Device communication in 5G networks by combining AES encryption with Huffman coding techniques and achieving enhanced security for D-2-D (Device to Device) communication while maintaining efficient data transmission. The AES method is known for protecting Device-to-Device (D2D) communication in 5 Generation networks. An effective security solution is provided by the AES algorithm for D-2-D (Device to Device) communication in 5 Generation networks, guaranteeing the secrecy of data exchanged between devices. This work enhances the privacy of D-2-D (Device to Device) communication, making it suitable for 5 Generation networks and it provides robust encryption of data while Huffman coding reduces the data size for efficient transmission using Python programming language.